Avaliação de atletas adolescentes de voleibol: estilo parental, estresse, humor e autoestima - Manfrinati, Luís Eduardo D'Almeida [UNIFESP] (2016)
Any type of sports development requires: knowledge and following established rules; specific psychomotor skills learning; concentration and attention to the movements; regular training; discipline and dedication. Objective: To study the family relations and psychological characteristics of adolescent athletes that participate in volleyball competitions. The specific aims were to measure the paternal and maternal parenting style; to evaluate the levels of stress, anxiety, humor and self-esteem. Methods: It is a comparative and quantitative study, split in two studies: Study 1 sample was formed by 30 volunteers, 15 athletes (GA) and 15 non-athletes (GNA), in a cross-case study. The instruments were Volunteer description, socioeconomic classification, Rosenberg?s self-esteem scale (EAR), Brunel?s mood scale (BRUMS), State-Trait Anxiety Inventory 6 (IDATE), Stress Scale for Adolescents (ESA) and Parental Behavior Inventory. The Study 2 sample was formed by 13 athletes, it?s a longitudinal study in four stages. Instruments: Competitive State Anxiety Inventory 2R (CSAI-2R),Brunel?s mood scale (BRUMS). The study was approved by the Ethics Committee of the Federal University of São Paulo (664.979). Results: In Study 1 the mother was identified by the GA group as the best relationship they had (80%) while in the GNA group both parents had the same percentage (53,3%). The groups presented predominance of positive parental behavior in comparison with the negative, except in the GNA?s maternal behavior. The anxiety levels of both groups were low and the stress scores indicated no signs of clinical disorders in either groups. The mood, the mental confusion, depression, fatigue were lower than vigor. The two groups differed statistically in self-esteem, mental confusion and vigor. GNA?s selfesteem and mental confusion were higher than the GA?s, although GA?s vigor scores were superior. As regards Study 2 the athletes obtained higher scores in competitive mood and anxiety in the opening stage "away from home?. However, lower scores were reached in the third stage, semi-final "at home", after a good performance on the previous stage. The principal discover was the different between the tension at opening and the other stages, which were related to the parental behavior from Study 1. Conclusion: It was noted the importance of parenting styles in the sporting development of adolescents, as well as the impact of the competitive environment in cognitive expression and the emotional reactions of young athletes.